2002
DOI: 10.1002/1521-396x(200211)194:1<118::aid-pssa118>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Electrical and Dielectric Properties of (Ca, Ta)-Doped TiO2 Varistors

Abstract: (Ca, Ta)‐doped TiO2 varistors with high nonlinear coefficients were obtained by ceramic sintering process. The nonlinear electrical and dielectric properties of the samples doped with 1.0 mol% Ca and different concentrations of Ta (0.05–2.0 mol%) were investigated. Especially, the effects of Ta dopant on the nonlinear and dielectric properties of the (Ca, Ta)‐doped TiO2 varistors were studied in detail. When the concentration of Ta is 0.5 mol%, the sample possesses the highest nonlinear coefficient (16.6). By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(11 reference statements)
1
1
0
Order By: Relevance
“…The resulting model is consistent with the experimental observations in the case of ZnO, TiO 2 and SnO 2based varistors [6][7][8][9]. It makes plausible our hypothesis on the existence of two types of the traps levels and on the variation of their respective occupation.…”
Section: Discussionsupporting
confidence: 89%
“…The resulting model is consistent with the experimental observations in the case of ZnO, TiO 2 and SnO 2based varistors [6][7][8][9]. It makes plausible our hypothesis on the existence of two types of the traps levels and on the variation of their respective occupation.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have shown that the structure of materials encapsulated in CNTs is very different from that of freestanding materials without any confinement. [15][16][17][18][19][20][21][22][23][24][25][26][27] The difference in structure or morphology of confined NWs is primarily due to the elastic energy caused by a mismatch between intrinsic length scale of solid (bond length, lattice constants, etc) and the dimension of confinement space. In order to find the reason for the difference in the structure, it is important to give a convincing description of the elastic energy.…”
Section: Introductionmentioning
confidence: 99%